2011
DOI: 10.1027/1864-1105/a000026
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Entertainment

Abstract: This essay explores the relationship of emotion and cognition in entertainment experience. Drawing on the reflective model of aesthetic experience (Cupchik, 1995) and the concept of appreciation (Oliver & Bartsch, 2010), we propose a multi-level view of affective processing that includes simple affect schemata as well as more elaborate forms of sociomoral reasoning that build on this basic layer of emotional meaning. To better understand how affective factors can stimulate or impede cognitive elaboration proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…Appreciation responses are characterized by self-reflection, self-acceptance, self-development, and personal growth as a result of observing characters' experiences (Bartsch, 2012;Bartsch & Oliver, 2011;Oliver, 2008;Oliver & Bartsch, 2010;Wirth, Hofer, & Schramm, 2012). For example, the negative affect generated by watching characters' misfortunes in a tragic film was shown to trigger reflection regarding one's own self, personal relationships, and life happiness, which then produced "tragedy enjoyment" (Knobloch-Westerwick, Gong, Hagner, & Kerbeykian, 2013).…”
Section: Character Morality and Enjoymentmentioning
confidence: 99%
“…Appreciation responses are characterized by self-reflection, self-acceptance, self-development, and personal growth as a result of observing characters' experiences (Bartsch, 2012;Bartsch & Oliver, 2011;Oliver, 2008;Oliver & Bartsch, 2010;Wirth, Hofer, & Schramm, 2012). For example, the negative affect generated by watching characters' misfortunes in a tragic film was shown to trigger reflection regarding one's own self, personal relationships, and life happiness, which then produced "tragedy enjoyment" (Knobloch-Westerwick, Gong, Hagner, & Kerbeykian, 2013).…”
Section: Character Morality and Enjoymentmentioning
confidence: 99%
“…A number of empirical studies, using the LC4MP's theoretical framework, demonstrated the aforementioned relationships, finding the positive effects of negative emotion on memory in moderate arousal levels but its adverse effects in high arousal levels in various media (e.g., television, radio, print and the Internet) and contexts (e.g., over-the-counter drug ads and health-related public service announcements; Bartsch & Oliver, 2011;Dardis, Schmierbach, & Limperos, 2012;Gibbons, Lukowski, & Walker, 2005;Lang, 2006;Lee & Lang, 2009;Norris, Bailey, Bolls, & Wise, 2012;Potter, 2009;Yegiyan & Lang, 2010). In a multimedia learning context, Chung F I G U R E 1 The relationship among motivational systems, emotion and cognition (e.g., Lang, 2006) 2.3 | Research questions…”
Section: Emotion and Memory-based Learningmentioning
confidence: 99%
“…Drawing on Kahneman's (2011) distinction of two systems of cognitive processing, Vorderer and Reinecke (2012) have argued that hedonic entertainment experience is characterized by fast, automatic, and effortless processing (System 1), whereas eudaimonic entertainment experience requires more attentive, systematic, and effortful processing (System 2). In a similar vein, Bartsch and Oliver (2011) have linked hedonic and eudaimonic entertainment experiences to dual-process models of cognitive processing that distinguish between peripheral vs. central processing (Petty & Cacioppo, 1986), heuristic vs. systematic processing (Chaiken et al, 1989), or automatic vs. controlled processing (A. Lang, 2006).…”
Section: The Concept Of Entertainment: Hedonic and Eudaimonic Approachesmentioning
confidence: 99%
“…Other models of hedonic entertainment share a focus on similar factors, specifically positive valence and excitatory potential, including theories of sensation seeking (Zuckerman, 1979), excitation transfer (Zillmann, 1996), and affective disposition (Zillmann & Cantor, 1977). Thus, an analysis of theoretical links between mood management factors and theories of motivated information processing may help elucidate the conceptual link between hedonic entertainment and automatic processing, as assumed by Vorderer and Reinecke (2012) and Bartsch and Oliver (2011).…”
Section: Hedonic Entertainment and Motivated Information Processingmentioning
confidence: 99%